A Utilização Dos Textos Humorísticos No Ensino De Língua Portuguesa (PERcursos Linguísticos, 2023)
This article aims to examine how humorous texts can be used in Portuguese language classes. To achieve this goal, we draw on theories from Textual Linguistics, addressing conceptions of language and communication (GERALDI, 1984), as well as studies by Koch (2004) and Elias (2016) to demonstrate that the text needs to be a multifaceted entity where meaning is constructed through interaction. Additionally, we rely on theories of humor by Berson (1983[1900]) and Raskin (1985) to identify how humor is triggered in the presented questions. Finally, we present three questions provided in the diagnostic assessment for 6th-grade students in the municipality of Vila Velha, which utilize humorous texts as support.